The Occurrence of Laryngeal Penetration and Aspiration in Patients with Glottal Closure Insufficiency. (11th March 2014) - Rajaei, Ali; Barzegar Bafrooei, Ebrahim; Mojiri, Fariba; Nilforoush, Mohammad Hussein
Abstract : Glottal closure during the pharyngeal phase of swallowing is one of the important steps in protecting the airway. Generally, it is believed that any deficiency in this process can lead to laryngeal penetration and aspiration. This study investigated the incidence of laryngeal penetration and aspiration among 44 patients with glottal closure insufficiencies that were referred for voice and swallowing evaluation to our institution. The videostroboscopy and 3 oz water swallow test were performed for all of the patients and dysphagic patients were screened and referred for videofluoroscopy. Overall, 15.90% of patients demonstrated signs of laryngeal penetration (13.63%) and aspiration (2.27%). The patients with the pattern of incomplete closure illustrated the highest percentage of penetration-aspiration (21.73%, 4.34%) among other GCI patterns. Thus, early interventions for these patients' swallowing condition seem necessary.